Temporal variations in QTc interval during and after COVID-19 infection: a retrospective study - Dasheng Lu; Jiancheng Hu; Jiahui Qian; Fangfang Cheng (BMC Cardiovascular Disorders)
Abstract Objective The aim of this study was to investigate the dynamic changes in QTc interval duration among patients with COVID-19 infection before, during, and after infection, in order to assess the short- and potential long-term impact of COVID-19 on cardiac electrophysiology. Methods A retrospective analysis was conducted on 303 inpatients diagnosed with COVID-19 who visited a tertiary Grade A hospital in China between August 2022 and December 2023. Inclusion criteria required patients to have at least two electrocardiogram (ECG) recordings at three specific time points: before COVID-19 infection, during acute infection, and after recovery (more than one month post-infection). Results The mean age of participants was 72.8 ± 14.7 years, with a male preponderance (62%, n = 188). A significant prolongation of QTc interval was observed during COVID-19 infection compared to pre-infection levels (438.3 ± 26.7 ms vs. 433.9 ± 26.6 ms, p = 0.025). QTc interval was positively correlated with age both before (r = 0.23, p = 0.001) and during infection (r = 0.19, p = 0.001). In short-term follow-up (≤ 6 months), QTc interval remained unchanged from the infectious period (p > 0.05), whereas it significantly decreased during long-term follow-up (> 6 months; 429.6 ± 32.5 ms vs. 437.5 ± 28.2 ms, p = 0.002). Additionally, P-wave duration significantly decreased from the infectious period to long-term follow-up (99.5 ± 14.8 ms to 96.4 ± 15.2 ms, p = 0.024). Conclusions COVID-19 infection demonstrated a significant correlation with prolonged QTc interval, persisting in the short term but gradually returning to normal in the long term. Similarly, P-wave duration shortened over time, suggesting potential cardiac electrophysiological recovery. Clinical trial number Not applicable.